Peran ilmuwan muslim dalam pengembangan sains modern: sebuah studi sejarah peradaban islam dari era keemasan ke era modern - nadifa, nur maghfirotun (Maliki Interdisciplinary Journal, 2026)
This study examines how Islamic knowledge developed and changed over time, particularly when the Abbasid Dynasty became the center of intellectual activity in Baghdad. Through a literature review of various historical sources and scientific studies, this study shows that scientific progress during this period was the result of a combination of scientific enthusiasm, a respect for foreign knowledge, and support for academic activities. Muslim scholars not only emphasized the lessons learned from previous research, but they also highlighted new discoveries that had a significant impact on mathematics, astronomy, medicine, and philosophy. The findings of this study demonstrate that, in this era, intellectuals have a crucial role in the progress of humanity and are highly relevant to the development of the Islamic tradition in the modern era.